The Effectiveness of Problem-Based Learning Model Assisted by Augmented Reality Media on The Motivation and Learning Outcomes - Shiva Febrianto, Devardo; Aeni, Kurotul (JTP - Jurnal Teknologi Pendidikan, 2024)
Learning Pancasila Education using the conventional model has an impact on low motivation and student learning outcomes in elementary schools. This research aims to determine the effectiveness of the problem-based learning model assisted by augmented reality media reviewed from motivation and learning outcomes of Pancasila education. This research uses a quasi-experimental research method (Quasi-Experimental Design), while the research design used is NonequValent Control Group Design. Data collection was carried out using questionnaire instruments to determine student motivation and multiple choices tests to determine students' Pancasila Education learning outcomes. The research sample was grade 5/B, totaling 21 students as the experimental grade and grade 5/A, totaling 20 students as the control grade. Research data analysis uses difference tests and data effectiveness tests. Results of the difference test with the independent sample t test with a tcount value of 2.882 for learning motivation and 2.483 for learning outcomes. The results of the effectiveness test used a one sample t test with a tcount value of 4.501 for learning motivation and 4.493 learning outcomes. The research conclusion is that the Problem Based Learning (PBL) model assisted by augmented reality (AR) media is effective in terms of motivation and learning outcomes for Pancasila Education.